2022
DOI: 10.3390/ijms231810870
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Affects Sphingolipid Metabolism in A549 Lung Adenocarcinoma Cells

Abstract: Resveratrol is a naturally occurring polyphenol which has various beneficial effects, such as anti-inflammatory, anti-tumor, anti-aging, antioxidant, and neuroprotective effects, among others. The anti-cancer activity of resveratrol has been related to alterations in sphingolipid metabolism. We analyzed the effect of resveratrol on the enzymes responsible for accumulation of the two sphingolipids with highest functional activity—apoptosis promoting ceramide (CER) and proliferation-stimulating sphingosine-1-pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…However, the level of S1P was gradually decreased in the following order of treatment: quercetin, fingolimod, quercetin + fingolimod, showing that the combined treatment produced a stronger effect on the level of S1P compared to each one of the individual treatments (Figure 4). Accordingly, in our previous studies we observed a decrease in the level of S1P in resveratrol-treated A549 lung adenocarcinoma cells [32]. However, Charytoniuk et al reported an increase of S1P in resveratrol-treated HepG2 cells in a lipid overload state, which might be related to a more complicated lipid metabolism in cells overloaded with lipid precursors [10].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…However, the level of S1P was gradually decreased in the following order of treatment: quercetin, fingolimod, quercetin + fingolimod, showing that the combined treatment produced a stronger effect on the level of S1P compared to each one of the individual treatments (Figure 4). Accordingly, in our previous studies we observed a decrease in the level of S1P in resveratrol-treated A549 lung adenocarcinoma cells [32]. However, Charytoniuk et al reported an increase of S1P in resveratrol-treated HepG2 cells in a lipid overload state, which might be related to a more complicated lipid metabolism in cells overloaded with lipid precursors [10].…”
Section: Discussionmentioning
confidence: 65%
“…There is evidence that another polyphenol, resveratrol, significantly affects the major sphingolipid metabolites in HepG2 cells [10]. What is more, in our recent paper, we reported that the effect of resveratrol on the lipid metabolism in A549 lung cancer cells is potentiated by combined treatment with fingolimod [32], which is why the latter was included in the present experiments. As evident from Figure 2 treatment of HepG2 cells with quercetin and fingolimod, alone or in combination, induced different effects on the level of SM.…”
Section: Discussionmentioning
confidence: 68%
“…Lung adenocarcinoma A-549 cells showed resistance to Triton X-100-mediated SM extraction before and after 50 μM/30 min ARA exposure. The SM membrane content of this cell line was also marginally affected following treatment with 100 μM resveratrol for 24 h [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol is one of the most studied polyphenols derived from plants. It modulates the SL pathway in a variety of cancers, including hepatocellular carcinoma, gastric cancer, lung adenocarcinoma, and leukemia [ 175 , 176 , 177 , 178 ]. Resveratrol was previously shown to cause apoptosis in HL-60 cells due to the accumulation of ceramides and a reduction in SPHK1 and GCS expression [ 178 ].…”
Section: Sls In Hematological Malignanciesmentioning
confidence: 99%